The Measurement of Emotional Intelligence: A Critical Review of the Literature and Recommendations for Researchers and Practitioners - O'Connor, Peter J.; Hill, Andrew; Kaya, Maria; Martin, Brett (Frontiers in Psychology, 2019)
Emotional Intelligence (EI) emerged in the 1990’s as an ability based construct analogous to general Intelligence. However over the previous 3 decades two further, conceptually distinct forms of EI have emerged (often termed 'trait EI' and 'mixed model EI') along with a large number of psychometric tools designed to measure these forms. Currently more than 30 different widely-used measures of EI have been developed. Although there is some clarity within the EI field regarding the types of EI and their respective measures, those external to the field are faced with a seemingly complex EI literature, overlapping terminology and multiple published measures. In this paper we seek to provide guidance to researchers and practitioners seeking to utilise EI in their work. We first provide an overview of the different conceptualisations of EI. We then provide a set of recommendations for practitioners and researchers regarding the most appropriate measures of EI for a range of different purposes. We provide guidance both on how to select and use different measures of EI. We conclude with a comprehensive review of the major measures of EI in terms of factor structure, reliability and validity.